Visualization Enhanced by Technology in the Learning of Multivariable Calculus - Habre, Samer (2001)
Visualization is the process of using geometrical illustrations of mathematical concepts. Over the past centuries, a decline in the geometric element in mathematical instruction has been observed. Computers have given mathematics the opportunity to adjust the balance between the various modes that constitute the basis of mathematical education: the symbolic, the visual, and the numeric. Visualization in multivariable calculus cannot be overemphasized. This paper is the outcome of observations compiled from a multivariable calculus class where computers were used extensively. Results show that visualization skills can be improved and that students use technology in very innovative ways.